A Socialization Program on the Introduction and Benefits of the TOEFL for Students of SMA Negeri 1 Pematangsiantar - Lumban Gaol, Daniel Binsah; Sirait, Tiofanny Elisabet; Situmorang, Arisdani Elman; Damanik, Jerico Devaly; Herman, Herman (Lembaga Penelitian dan Publikasi Ilmiah, Yayasan Almahmudi Bin Dahlan, 2025)
This study aims to socialize the importance and benefits of the TOEFL (Test of English as a Foreign Language) to the eleventh-grade students of SMA Negeri 1 Pematangsiantar. TOEFL is an internationally recognized English proficiency test that assesses four language skills: Listening, Reading, Speaking, and Writing. Among these, the Reading skill is crucial because it measures the ability to understand academic texts, identify main ideas, make inferences, and analyze information. These skills are important for students to succeed in academic environments and improve their overall English proficiency. The socialization program was conducted through seminars and interactive discussions involving 35 students at SMA Negeri 1 Pematangsiantar. The program provided information about the TOEFL test format, benefits, and preparation strategies, with special emphasis on improving reading comprehension skills. Data were collected through observations and questionnaires to evaluate participants’ understanding and motivation. Results indicated that students increased their awareness of TOEFL and the significance of the Reading section. However, challenges such as limited learning resources and insufficient practice opportunities were identified. The study recommends the integration of multimedia tools and continuous guidance to help students enhance their TOEFL reading skills. This program underlines the importance of TOEFL socialization in schools to prepare students for global academic challenges.